2014
DOI: 10.1002/jts.21972
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of 9/11‐Related PTSD and Depression in the World Trade Center Health Registry 10–11 Years Postdisaster

Abstract: Many studies report elevated prevalence of posttraumatic stress disorder (PTSD) and depression among persons exposed to the September 11, 2001 (9/11) disaster compared to those unexposed; few have evaluated long-term PTSD with comorbid depression. We examined prevalence and risk factors for probable PTSD, probable depression, and both conditions 10-11 years post-9/11 among 29,486 World Trade Center Health Registry enrollees who completed surveys at Wave 1 (2003-2004), Wave 2 (2006-2007), and Wave 3 (2011-2012)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
58
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 15 publications
(37 reference statements)
11
58
0
2
Order By: Relevance
“…Previous studies [Shalev et al, 1998;O'Donnell et al, 2004;Caramanica et al, 2014] report that PTSD with comorbid depression was more frequent than PTSD alone. However, these studies did not examine comorbid anxiety.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Previous studies [Shalev et al, 1998;O'Donnell et al, 2004;Caramanica et al, 2014] report that PTSD with comorbid depression was more frequent than PTSD alone. However, these studies did not examine comorbid anxiety.…”
Section: Discussionmentioning
confidence: 88%
“…Previous research has shown that psychiatric comorbidity is the rule rather than the exception for people with PTSD, and the presence of psychiatric comorbidity heightens the burden of mental illness, lowers psychosocial functioning, and is more likely to be chronic [Kessler et al, 2005;Wilk et al, 2006;Caramanica et al, 2014;Hruska et al, 2014]. Approximately, 75% of individuals with PTSD experience one or more comorbid disorders [Kaufman and Charney, 2000] and are 80% more likely than those without PTSD to develop another mental disorder [APA, 2013].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Понимание клинико-психологических последствий переживания террористической угрозы необходимо для разработки эффективных стратегий снижения негативных исходов воздействия угрозы терроризма на психику человека, среди которых наиболее часто выделяют стрессовые реакции, депрессию, расстройства сна, увеличение потребления психоактивных веществ. Результаты лонгитюдных исследований по-следствий терактов показывают, что интенсивность посттравматических симптомов, вызванных информацией о терактах, постепенно снижается для большей части социума и сохраняется у особой, уязвимой части общества [1]. В этих исследованиях продемонстрирована способность людей сохранять и поддерживать оптимальный уровень функционирования в экстремальных условиях, восстанавливаться после психотравмирующих событий.…”
Section: Risk Factors and Protective Resources In Resilience To A Terunclassified